Sexual Urges among Adolescent Students in Islamic Boarding Schools: Institutional Roles and Self-Regulation Strategies - Ade Syifani Nurmaidah; Septi Gumiandari (Research Horizon, 2026)
The phenomenon of sexual urges among adolescent students is part of their biological, psychological, and social development, alongside management challenges within restrictive Islamic boarding school environments. This study aims to analyze the forms of sexual urges, the institutional role, and students’ self-regulation strategies in managing these impulses. Employing a qualitative approach with a case study design, data were gathered from eight informants through observation, in-depth interviews, and Miles and Huberman analysis. The results indicate that students experience sexual urges through emotional attraction, physical impulses, and imagination that disrupt learning concentration but are manageable via internalizing religious values, routine worship, cognitive control, and social support. This study concludes that Islamic boarding schools play a vital role in fostering student self-regulation, enabling them to manage sexual urges adaptively according to Islamic values. The implications underscore the importance of reinforcing religious and psychologically based guidance programs to holistically support students’ moral, social, and spiritual development, serving as a reference for character education policies.